HeForShe in HFE: Strategies for Enhancing Equality in Leadership for All Allies. (November 2019) - Stowers, Kimberly; Hancock, Gabriella M.; Neigel, Alexis; Cha, Jackie; Chong, Isis; Durso, Francis T.; Peres, S. Camille; Stone, Nancy J.; Summers, Baron
The objective of this panel is to highlight past efforts that have successfully enhanced leadership of women in HFE, as well as brainstorm ideas for continuing this process in the future. In particular, this panel builds off the United Nations' "HeForShe" movement, which addresses gender equality as a human rights issue in which everyone can take part. As part of this panel, we aim to provide cross-sectional strategies for fostering gender equality, as well as brainstorm future initiatives that take into account the continuing social shifts in gender perceptions. The panel will be co-chaired by Drs. Kimberly Stowers and Gabriella Hancock with assistance from Dr. Alexis Neigel, who will introduce the panel and its role in the HF/E Women's Organization for Mentoring and Networking's larger campaign to foster fair and inclusive professional development for future leaders. A variety of panelists from different genders, professional stages, and backgrounds will offer their unique perspective(s) on leadership and professional development. Members of the audience are encouraged to come prepared with questions to better learn the panelists' thoughts, opinions, and strategies concerning what could and should be done to encourage women's leadership in the future. Drs. Hancock and Stowers will foster discussion amongst the panelists, and invite questions and participation from the audience.